Design and characterization of enzymatic deglycosylation systems to produce drugs against Alzheimer’s disease - Vila Real, Helder João Ferreira, 1982- (2011)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2011